The Importance of Instilling Tawhid in Children from an Early Age - Mariam Mariam; Moh Safik Al Mubarok (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
Instilling tauhid in young children is the main foundation for shaping a strong Muslim personality. Children in their early years are in a golden phase of spiritual and moral development, so tauhid education is very important to be applied from an early age. This study aims to identify the basic concepts of tauhid suitable for young children, understand its urgency, and explore effective methods in the process of instilling it. A qualitative approach was used, involving literature review and analysis of educational practices in Islamic early childhood education institutions. The results of the study indicate that methods such as storytelling, habit formation, modeling, and educational games based on Islamic values are effective strategies. The early instillation of tauhid plays a significant role in shaping children's spiritual character and strengthening moral values that will carry them into adulthood. However, this study also identified limitations in educational materials suitable for children's developmental stages and a lack of teacher training in conveying tauhid concepts in an applied manner, which pose challenges in its implementation